Analisis hasil belajar fisika siswa ditinjau dari persepsinya terhadap pembelajaran pada materi hukum newton tentang gerak di kelas X SMA di kota Padang - Heri Yanto; Amali Putra (PILLAR OF PHYSICS EDUCATION, 2020)
The results of the analysis of the documentation of physics learning outcomes of class X students in the city of Padang, showed that student learning outcomes on Newton's Law of Motion occupied the lowest value compared to other material. This shows that in the learning process students get various difficulties. This study aims to a) determine the tendency of students 'perceptions of physics learning on Newton's law material about motion, b) determine the quality of student learning outcomes on Newton's law material about motion, c) the contribution of students' perceptions of physics learning on Newton's law material about motion towards results student learning in the semester January-June 2019, and d) reveal various problems experienced by students in the physics learning process in terms of perception. This research belongs to the type of correlational descriptive research. The research sample was drawn using Stratified Random Sampling technique. The number of samples obtained was 60 students representing students with high, medium and less grades who came from 4 public high schools and 1 private high school. Research data on perceptions were obtained using an instrument in the form of a questionnaire consisting of 60 items of statements and learning outcome data obtained through 24 items arranged based on 4 dimensions of knowledge and 6 levels of cognitive processes in the revised Bloom taxonomy. The research instrument used has fulfilled the feasibility through its validity and reliability test. Data processing is done through percentage techniques and Pearson Product Moment correlation analysis after fulfilling the test requirements for analysis, normality and linearity. The results showed that a) the students' average perception of learning physics in Newton's law material about motion was in the high category with a value of 2.74 from a maximum value of 4, b) student's physics learning outcomes in Newton's law material about motion in the low category with an average value of 48, c) there is a significant positive relationship between students' perceptions with their learning outcomes in Newton's law material about motion with a contribution of 61.3%, and d) revealed 10 factors that cause students difficulty in learning Newton's law material about motion according to students' perceptions.